„Stargana za trzewia publiczność opadła jak jeden flak”. Witkacego spektakle potencjalne - Gondowicz, Jan (Wydawnictwo Naukowe UAM w Poznaniu, 2010)
Witkacy’s well-known Pure Form in Theatre Theory constitutes, from the logical point of view, a sequence of paradoxical definitions and surrealistic examples. It is, undoubtedly, a premeditated tactics of the Author. Witkacy deliberately aspired to make a mess in the reader's (or, in fact, implied spectator’s) brain, and discreetly intervowen in principal specimen’s content own anthropological experience, collected in an Australian expedition. Finally, in the visionary novel Insatiability, Witkacy smashed up his concept of metaphysical theatre, impossible in the future stupefied society
“The gut-wrenched audience sank back into their seats like one limp intestine”**. Witkacy’s Potential Performances